Impact of Indian Journal of Veterinary Anatomy through Google Scholar - Kutty Kumar; T.S.Chandrasekhara Rao; Archana Pathak; Pawan Kumar (Indian Journal of Veterinary Anatomy, 2025)
A Scientometric research of the Indian Journal of Veterinary Anatomy (IJVA) was undertaken between 1990 and 2023 utilizing the Publish or Perish (PoP) software platform. The data for 34 years collected for the study. The influence of Indian Journal of Veterinary Anatomy (IJVA) on contemporary academic research was assessed by extracting unprocessed data from Google Scholar and employing 12 h-Index metrics to analyse it. The study analyzed 658 scientific articles to investigate Zipf's Law in relation to annual contributions, authorship patterns and author productivity trends. The study period also involved an examination of IJVA's relative growth rate and doubling time. Based on our data, the year 2018 had the highest number of publications, with 62 articles, accounting for 9.42% of the total publications. The examined impact rankings of IJVA are presented as an average. The current study utilised data from many sources, including indexes (h and g), h-index, g-index, papers, citations, years, citations per year, citations per paper, citations per author and papers per author.